Chemical solution deposition of la-substituted BiFe0.5Sc0.5O3 perovskite thin films on different substrates - Griesiute, Diana (2021)
In the present work, polycrystalline Bi0.67La0.33Fe0.5Sc0.5O3 thin films were synthesized using a simple and cost‐effective chemical solution deposition process employing the spin coating tech‐ nique. In order to check the feasibility of the fabrication of thin films on various types of substrates, the films were deposited on Pt‐coated silicon, silicon, sapphire, corundum, fused silica and glass. Based on the results of thermogravimetric analysis of precursor and thermal stability study, it was determined that the optimal annealing temperature for the formation of perovskite structure is 600 °C. It was observed that the relative intensity of the pseudocubic peaks (001)p and (011)p in the XRD patterns is influenced by the nature of substrates, suggesting that the formed crystallites have some preferred orientation. Roughness of the films was determined to be dependent on the nature of the substrate.